Publish or patent? Knowledge dissemination in agricultural biotechnology - Michiels, An; Koo, Bonwoo (International Food Policy Research Institute, 2008)
Plant transformation research has achieved outstanding progress in the development of transgenic crops over the past decades, and the research results have been spread through journal publications and patents. With the recent emergence of stronger intellectual property rights, investments in crop research and the landscape of plant transformation research have changed, along with the patterns of knowledge dissemination. In this paper, we discuss the recent trends in plant transformation research by examining patent and journal publication data during the last decade. The data analysis shows that there have been significant shifts toward applied research by developing countries and toward patenting as a means of knowledge dissemination during the past few decades, reflecting the increasing role of the private sector in developing countries in crop improvement research.